Acute and subacute toxic study on mice of glipizide synthesized in Viet Nam - Bui, Thi Thoi; Ngo, Dai Quang; Tran, Van Loc; Tran, Van Chien; Nguyen, Thi Nga; Do, Thi Thao (Vietnam Journal of Science and Technology, 2019)
Glipizide is a second generation of sulfonylurea with promising hypoglycemic activity. It acts by stimulating the release of insulin from β-cells of pancreas. Glipizide is absorbed rapidly, uniformly with good mean oral bioavailability. It offers several advantages such as swift and short action, high potency and also does not accumulate in plasma on repeated oral administration. In this paper we report the acute and subacute toxicity of glipizide on BALB/c albino mice. The results showed the safety of our synthesized products.